Extravasation of Antineoplastic Drugs in Pediatric Patients: Algorithms for Prevention, Treatment, and Follow-Up - Chanes, Daniella Cristina (2008)
Introduction: Extravasation of antineoplastic drugs is one of the most severe acute reactions related to intravenous administration of such treatment. Standardized nursing care for drug administration and intervention in case of extravasation is important for assuring patient safety. Objectives: The objectives were to identify studies in the literature related to extravasation of antineoplastic drugs in children and adolescents and to develop algorithms for prevention, treatment, and follow-up of this adverse event. Methods: A literature search was performed in MEDLINE, PUBMED, and LILACS from 1993 to 2005. Key words searched were: extravasation, antineoplastic drugs, children, and follow-up. Results: Twelve studies were selected and grouped into three issues: prevention; nursing intervention and treatment; and follow-up and notification. Some risk factors for extravasation in children are described, emphasizing the effectiveness of the non-pharmacological treatment of this adverse event. The studies also highlighted that suspected or confirmed extravasation must be followed with specific instruments and protocols. Based on the findings in the literature, two algorithms were developed for nursing care for patients undergoing chemotherapy. Conclusion: Extravasation of antineoplastic drugs can be either prevented or diagnosed earlier, and nursing intervention and follow-up can be managed better using established institutional protocols.